Transformasi Digital UMKM Sebagai Kunci Sukses di Pasar Internasional - Muhamad Rudi Saputra Pratama; Munawaroh (Trending: Jurnal Manajemen dan Ekonomi, 2025)
Digital transformation is key for micro, small and medium enterprises (MSMEs) to be more competitive in the global market. Although MSMEs contribute significantly to GDP and job creation, they face significant challenges due to rapid globalization and technological pressures. This study systematically reviews the literature on MSME digital transformation and identifies benefits such as increased operational efficiency and international market access, as well as challenges such as limited resources and resistance to change. The study uses the Systematic Literature Review (SLR) methodology and the PRISMA framework to highlight the importance of digital capabilities and ecosystem support in the digitalization process. The results show that MSME digital success depends on visionary leadership, appropriate technology infrastructure, and adaptive organizational culture. Digital transformation is critical to the survival and success of MSMEs in the international market, as digital transformation not only enhances their competitiveness but also drives innovation and sustainability.